2020
DOI: 10.18502/avr.v29i2.2794
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the reliability of the Persian version of the tinnitus functional index in a military population

Abstract: Background and Aim: Tinnitus functional index (TFI) has been introduced as a standard self-assessment questionnaire for the evaluation of tinnitus severity and its negative consequences with enough sensitivity to detect the outcomes of treatment. The purpose of this study was to translate the original tinnitus functional index into Persian and to evaluate its reliability in a military population. Methods: The translation was performed in accordance with the Principles of Good Practice for the Translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results of present study revealed that there was a significant relationship between the scores of TFI-P and THI-P. This is consistent with the results of other studies such as Meikle et al for the original version [6], Fackrell et al for the [7]. The present study showed lower correlation level between THI-P and TFI-P scores compared to similar studies reported for other language versions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of present study revealed that there was a significant relationship between the scores of TFI-P and THI-P. This is consistent with the results of other studies such as Meikle et al for the original version [6], Fackrell et al for the [7]. The present study showed lower correlation level between THI-P and TFI-P scores compared to similar studies reported for other language versions.…”
Section: Discussionsupporting
confidence: 92%
“…Tinnitus functional index (TFI) and tinnitus handicap inventory (THI) are the two most used tinnitus questionnaires. TFI was designed by Meikle et al [6] and was translated into Persian by Mahdavi et al and its' reliability was investigated in military population [7]. TFI was the first questionnaire for monitoring the patients' responses to treatment [8].…”
Section: Introductionmentioning
confidence: 99%